Deep granuloma annulare - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Deep granuloma annulare is second for frequency after localized superficial granuloma annulare; more rare is in the child disseminated granuloma annulare, while perforating granuloma annulare is exceptional. The most frequent sites of superficial granuloma annulare are the dorsal aspect of the feet and hands, and the fingers, while deep granuloma annulare affects mainly the legs and forearms. Deep granuloma annulare presents as a subcutaneous nodule, with not well defined limits, hard-elastic, painless and movable on the deep planes. Radiological and MRI characteristics are not specific and are not useful for the diagnosis (1, 2). On the other hand, the latter is made easier by the simultaneous presence of a localized superficial form. Deep granuloma annulare, as the superficial one, regresses spontaneously in about two years, but recurrences are possible.